ANALISIS FAKTOR PENENTU AKUNTABILITAS PENGELOLAAN DANA DESA DI KECAMATAN GATAK, KABUPATEN SUKOHARJO - Dilla Andreani Kusuma Dewi; Yuwita Ariessa Pravasanti; Desy Nur Pratiwi (CV. Denasya Smart Publisher, 2026)
This study aims to examine the influence of human resource competency, the government internal control system (SPIP), and the use of digitalization on the accountability of village fund management in Gatak District, Sukoharjo Regency. The population consisted of village officials directly related to village fund management from 14 villages with a total of 140 village officials. Sampling used a purposive sampling technique. This study was quantitative by distributing questionnaires to respondents as data collection. The data analysis technique was carried out using multiple linear regression with the help of SPSS version 23 software, which includes validity tests, reliability tests, classical assumption tests, F tests, t tests, and coefficients of determination (R²). The F test results show that simultaneously, all three variables significantly affect the accountability of village fund management. The t test results indicate that, individually, human resource competence, government internal control system (SPIP), and the use of digitalization each have a positive and significant impact on the accountability of village fund management, so all the hypotheses in this study are accepted.